Requirements for the success of tourism marketing as a mechanism to enhance the competitiveness of the tourism sector in Algeria - Tahar Chelihi; Ali Azzedine (Journal of Excellence for Economics and Management Research, 2019)
The tourism sector is an important sector that has a direct impact on increasing national income. The tourism sector has become the focus of many countries in diversifying their sources of income, relying on a variety of mechanisms including what is known as tourism marketing. This concept would provide upscale tourist experiences In the context of the efforts to be relied upon in the formulation of marketing programs and policies and the promotion of various tourism services.Through this study we seek to highlight the importance of tourism marketing and the most important requirements for its success to promote the tourism sector in Algeria in the light of the plans related to tourism